Identification of resistance sources in common bean (Phaseolus vulgaris) genotypes from Turkey and the reactions of some promising genotypes to bean anthracnose (Colletotrichum lindemuthianum) - Palacıoğlu, Gülsüm; Yeken, Mehmet Zahit; Kantar, Faik; Cancı, Hüseyin; Çiftçi, Vahdettin; Bayraktar, Harun; Özer, Göksel (CSIRO PUBLISHING, 2022)
Context Among biotic factors, bean anthracnose caused by Colletotrichum lindemuthianum (Sacc. & Magnus) Briosi & Cavara is one of the most destructive diseases of common bean (Phaseolus vulgaris L.). Resistance in common bean genotypes is controlled by anthracnose resistance loci (designated Co). Aims The objective of this study was to evaluate the presence of Co resistance genes in common bean genotypes from Turkey and to examine promising genotypes as candidates for parent plants in breeding studies. Methods The presence of Co resistance genes in 693 common bean genotypes from 35 provinces of Turkey was determined by 12 SCAR (sequence characterised amplified region), RAPD (random amplified polymorphic DNA), STS (sequence-tagged site) and CAPS (cleaved amplified polymorphic sequence) markers. The disease reaction of 40 agronomically promising genotypes to different pathogen isolates was evaluated in a pot study. Key results The results indicated the presence of Co-1, Co-1(4), Co-1(5), Co-2, Co-3(3), Co-4, Co-4(2), Co-6, Co-10, Co-11 and Co-13 resistance genes, alone or in combination; Co-5 was not detected in any of the genotypes. Among the genotypes, Co-1(5) was the most frequent resistance source, followed by Co-4, Co-6 and Co-11, respectively. Common bean genotypes carrying Co-1(4), Co-2, Co-3(3), Co-11 and Co-13 have been identified for the first time in Turkish germplasm. Five genotypes carrying the various combinations of Co-1, Co-1(5), Co-4, Co-6, Co-10, Co-11 and Co-13 were resistant to all isolates in pathogenicity tests. Conclusions This study is the most comprehensive to date on Co genes linked to the resistance of common bean genotypes throughout Turkey and provides an important gene pool for breeding studies into bean anthracnose. Resistant genotypes identified will be useful as parent plants in resistance breeding studies. Implications Resistance genotypes carrying different Co genes to bean anthracnose will contribute significantly to the disease management strategy.
Keywords: bean anthracnose; Co genes; Colletotrichum lindemuthianum; common bean; disease reaction; gene pool; genitor plant; molecular